Allergic Potential of Medicinal Plants From the Asteraceae Family - Tim Ključevšek; Samo Kreft (Health Science Reports)
ABSTRACT Background and Aims The popularity of herbal medicine continues to increase in modern health care practices; therefore, it is imperative to recognize and address potential risks associated with its everyday use. The Asteraceae family is one of the most extensively utilized medicinal plant families due to its abundance and diversity of bioactive secondary metabolites. The aim of this article is to review the current understanding of the allergic potential of the most significant medicinal plant species belonging to the Asteraceae family. Methods This review utilized various search engines, including PubMed Central, Cochrane Central, Google Scholar, and others, up to January 2024, considering only articles in English. Results Asteraceae have long been acknowledged as important sensitizers within occupational environments, eliciting both immediate and delayed hypersensitivity reactions. Recent investigations have indicated the presence of panallergens in Asteraceae pollen, predominantly identified in Ambrosia artemisiifolia and Artemisia spp., which are pervasive across many species within the family. These panallergens contribute to cross‐reactivity phenomena, serving as primary triggers for pollinosis and pollen‐food or pollen‐medicine allergy syndrome. In addition, the diverse array of secondary metabolites present in the Asteraceae family, particularly sesquiterpene lactones (SLs), possesses sensitizing properties capable of inducing skin irritation and inflammation. Moreover, SLs have the potential to incite systemic reactions, posing a risk to sensitized individuals upon ingestion. Although extensive cross‐reactivity among SLs has been reported, further investigations are warranted to elucidate the underlying mechanisms and implications. Conclusion As numerous uncertainties persist regarding critical Asteraceae allergens and sensitizers further research is critical to augment our understanding of the potential risks posed by Asteraceae herbal medicine.